2018
DOI: 10.13189/eer.2018.060103
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Adaptation Strategies to the Impacts of Climate Change: A Case Study of Pungu - Upper East Region, Ghana

Abstract: The research was undertaken at Pungu in the Kassena Nankana Municipal Assembly in the Upper East Region of Ghana, in order to assess the adaptation strategies of the impacts of climate change by indigenes with respect to the unpredictable change in climate at the area (Pungu). The study was based on climate change impact on health, water resources, agriculture and socioeconomic statuses as questionnaire and interview were the scientific methods utilized in this findings. The results from the assessment showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…This ensures that an amount of water stays at that point which is then used for irrigation. According to [20], most farmers in the northern sector of Ghana use shallow wells or hand-dug wells alongside boreholes and rainwater collection during the rainy season for use during the dry season. This finding confirms the results of the current study and also indicates that this practice is widespread and a proven adaptation strategy for water conservation in northern Ghana because of the unimodal rainfall pattern.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ensures that an amount of water stays at that point which is then used for irrigation. According to [20], most farmers in the northern sector of Ghana use shallow wells or hand-dug wells alongside boreholes and rainwater collection during the rainy season for use during the dry season. This finding confirms the results of the current study and also indicates that this practice is widespread and a proven adaptation strategy for water conservation in northern Ghana because of the unimodal rainfall pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Findings by other researchers, based on field surveys, agree with those of this study. For instance, a survey conducted by [20] reported that about 90% of respondents indicated the growing of vegetables as a good strategy for climate change adaptation. By so doing, the farmers can sell the vegetables and then buy other basic needs for the family.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, households are food insecure in terms of grain shortage and poor nutritional diversity (Owusu et al, 2013). One study emphasized that household members had attempted to escape from this difficulty by moving to urban areas (Ampadu et al, 2018). In particular, out-migration among the youths in small communities has increased (Adam et al, 2016).…”
Section: Methodology the Study Areamentioning
confidence: 99%
“…Climate change is being experienced through an increase in global temperatures, sea-level rise, shrinking ice sheets, warming oceans, Arctic sea ice decline, glacial retreat, increasing extreme events, ocean acidification, and decreased snow cover [ 6 ]. Climate change may affect human health in many ways, including affecting livelihood and food security [ 7 , 8 ]. In addition, climate change could directly influence the patterns of infectious diseases and vector-borne diseases [ 9 ] and modify vector distribution and the extension of geographical ranges of mosquitoes such as the malaria vector [ 10 ].…”
Section: Introductionmentioning
confidence: 99%